Effects of probiotic supplements on cognition, anxiety, and physical activity in subjects with mild and moderate Alzheimer’s disease: A randomized, double-blind, and placebo-controlled study - Akhgarjand, Camellia; Vahabi, Zahra; Shab-Bidar, Sakineh; Etesam, Farnaz; Djafarian, Kurosh (Frontiers in Aging Neuroscience, 2022)
Probiotics has been suggested as an effective adjuvant treatment for Alzheimer’s disease (AD) due to its modulating effect on the gut microbiota, which may affect the gut-brain axis. Therefore, we aimed to evaluate the effects of two different single-strain probiotics on cognition, physical activity, and anxiety in subjects with mild and moderate AD. Eligible patients (n=90) with AD were randomly assigned to either of two interventions (Lactobacillus rhamnosus HA-114 (1015 CFU) or Bifidobacterium longum R0175 (1015 CFU)) or placebo group, receiving probiotic supplement twice daily for 12 weeks. The primary outcome of the study was cognitive function measured by using two tests; the Mini-Mental State Exam (MMSE) and the Categorical verbal fluency test (CFT). Secondary outcomes included performance in Activities Daily Living (ADL), the Lawton Instrumental Activities of Daily Living (IADL) scale and the Generalized Anxiety Disorder scale (GAD-7). Linear mixed-effect models were used to investigate independent effects of probiotics on clinical outcomes. After 12 weeks, MMSE significantly improved cognition (PInteraction ˂0.0001), with post hoc comparisons identifying significantly more improvement in the Bifidobacterium longum intervention group (Differences: 4.86, 95%CI: 3.91- 5.81; P ˂0.0001) compared with both the placebo and Lactobacillus rhamnosus intervention group (Differences: 4.06, 95%CI: 3.11- 5.01; P ˂0.0001). There was no significant difference between the two intervention groups (Differences: -0.8, 95%CI: -1.74- 0.14; P= 0.09). In conclusion, this trial demonstrated that 12-week probiotic supplementation compared with placebo had beneficial effects on the cognition status of AD patients, GAD and IADL.